Improving Science Learning Outcomes Through Picture Media Props for Class V Elementary School Students - Ronaldi Ronaldi (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
The author's purpose to improve this learning is to improve student understanding and learning outcomes about the material "Grouping Animals Based on Types of Food" through media images that are in accordance with the environment where students live in science lessons for class V SDN 02 Matotonan, South Siberut sub-district. This research design follows a cyclical research model that refers to the classroom action research design. The lesson plan was made in III cycles. In the lesson plans for each cycle, improvements are made that are adjusted to the level of achievement of understanding the material presented based on the results of student evaluation scores. From the research conducted, student learning outcomes increased from each stage of the implementation of learning with an average pre-cycle classical of 50, increased to 63.15 in the first cycle, and increased again to 85.78 in the second cycle. By using the right paraga, namely media images that are in accordance with the student's environment in science learning, it will make the learning more interesting, fun and more effective. Making students more active and the material presented is more easily absorbed by students so that it has an impact on student learning outcomes that are increasingly satisfying.